Childhood-onset form of myotonic dystrophy type 1 and autism spectrum disorder: Is there comorbidity? - Angeard, N; Huerta, E; Jacquette, A; Cohen, D; Xavier, J; Gargiulo, M; Servais, L; Eymard, B; Héron, D (Elsevier, 2017)
Myotonic dystrophy type 1 (DM1) is a multisystemic disorder with neuromuscular symptoms and brain dysfunctions. Depending on the phenotypic expression, the degree of cognitive impairment remains heterogeneous, ranging from moderate to severe intellectual disability in the congenital form, to executive, visuospatial and personality dysfunction in the adult-onset form. Studies exploring the cognitive or psychiatric impairments in the childhood form of DM1, characterized by an age of onset between one and ten years, uneventful pre and post natal history and normal development the first year of life, are scarce and show conflicting results in regard to a comorbid diagnosis of Autism Spectrum Disorder (ASD). The aim of the current review is to summarize diagnostic criteria and update the state of the debate regarding comorbidity. Evidence from 9 studies collected in PubMed database (representing a total of 175 cases) focusing on clinical, neuropsychological and neuroimaging domains in childhood DM1 is considered and similarities or differences between childhood DM1 and ASD are identified. Highlighting what is known about the neurocognitive features specific to the childhood-onset form of DM1 could help (1) propose early screening regarding socio-emotional and attentional/executive functions or (2) implement therapeutic programs based on reinforcement of executive skills or social cognition.